Measurement and correction of in vivo sample aberrations employing a nonlinear guide-star in two-photon excited fluorescence microscopy - Aviles-Espinosa, Rodrigo (Optical Society of America, 2011)
We demonstrate that sample induced aberrations can be measured in a nonlinear microscope. This uses the fact that two-photon excited fluorescence naturally produces a localized point source inside the sample: the nonlinear guide-star (NL-GS). The wavefront emitted from the NL-GS can then be recorded using a Shack-Hartmann sensor. Compensation of the recorded sample aberrations is performed by the deformable mirror in a single-step. This technique is applied to fixed and in vivo biological samples, showing, in some cases, more than one order of magnitude improvement in the total collected signal intensity.